Towards a Sustainable Future: The Emerging Role and Far-Reaching Impact of Green Finance Instruments in Russia-China Trade Relations - Wenkai Xie; Chunxiao Bi; N. P. Kuznetsova (Финансы: теория и практика, 2025)
In today’s context of globalization, the trade relationship between China and Russia has become increasingly close, and with the rising global concern for environmental sustainability, green finance, as an emerging financial model, is gradually becoming an important factor in Russia-China trade cooperation. This article explores the role and impact of green financial instruments in trade relations between China and Russia. It empirically analyses the relationship between the volume of exports to Russia from 22 Chinese provinces and variables such as the level of development of green financial instruments (green insurance, green credit, green bonds, green funds), GDP and population in each province. The results show that green credit, bonds and funds have no significant impact on export volume, while green insurance has a damping effect on export growth. China and Russia need to deepen cooperation in green finance, optimise green insurance policy formulation, reduce the burden on enterprises, and strengthen the market promotion and innovation of green financial instruments. It is recommended that both governments strengthen policy coordination, provide tax incentives and financial support, and promote the green transformation of trade structures to achieve synergistic development of the economy and the environment.